Nonmeasurable speckled contrast-enhancing lesions appearing during course of disease are associated with IDH mutation in high-grade astrocytoma patients - Berberich, Anne; Vollmuth, Philipp; Winkler, Frank; Drüschler, Katharina; Riedemann, Lars; Arzt, Marlene; Keßler, Tobias; Platten, Michael; Deimling, Andreas von; Wick, Wolfgang; Sahm, Felix; Bendszus, Martin; et al. (International journal of radiation oncology, biology, physics, 2018)
Purpose - Because treatment options at progression are limited for patients with glioma, accuracy in definition of progression is pivotal. Clinically asymptomatic, newly detected, nonmeasurable, speckled contrast-enhancing lesions (SCEs) without immediate relation to prior immune therapy or radiation therapy appear relatively frequently during the course of disease in patients with glioma and challenge the definition of progression based on Response Assessment in Neuro-oncology criteria. Therefore, data characterizing these SCEs are needed for recommendations of subsequent clinical management. - Materials and Methods - Magnetic resonance imaging of 746 patients with glioma included in this study were retrospectively revised for appearance of newly detected SCEs during the course of disease. Associations with molecular and clinical baseline parameters and their prognostic impact were statistically analyzed, and frequency, natural course, and location of SCEs were described. - Results - SCEs occurred more frequently in World Health Organization grade 2 and 3 astrocytoma and oligodendroglial tumors and were significantly associated with isocitrate dehydrogenase mutation in World Health Organization grade 3 astrocytoma and glioblastoma. SCEs mostly remained stable or dissolved in follow-up magnetic resonance imaging, even if no new treatment was initiated. SCEs were frequently located within the tumor or tumor-associated fluid-attenuated inversion recovery abnormalities, but distant appearance also occurred. In patients with glioblastoma, SCEs were associated with a favorable prognosis, which was also observed in the subgroup of patients with glioblastoma with isocitrate dehydrogenase wildtype status. - Conclusions - The data demonstrate a predominantly benign course of SCEs after their appearance and emphasize cautious definitions of progression and regular clinical and radiographic follow-up rather than premature initiation of new antitumor therapies until progression is confirmed.
Gesehen am 26.04.2019